Reducing Sedimentation in Catchment Areas as Part of the Revitalization Efforts at Batujai Reservoir in Central Lombok - Fahmi, Muhammad Arifudin; Wahyudi, Slamet Imam; Niam, Moh Faiqun (JACEE (Journal of Advanced Civil and Environmental Engineering), 2024)
This research discusses efforts to revitalize the Batujai Reservoir in Central Lombok with a focus on sedimentation problems. Batujai Reservoir has a strategic role in meeting water needs in the surrounding area, but faces serious challenges due to significant sedimentation. In addition to assessing the effects of these changes on the reservoir's benefits—such as irrigation, flood control, and electricity production—this study intends to examine the effects of land use changes in the Dodokan Sub-Watershed Catchment Area (DTA) on the features and volume of sedimentation entering the reservoir. In addition, this study attempts to develop suggestions for efficient sedimentation management plans in order to increase the Batujai Reservoir's service life. Research methods include primary and secondary data collection, sedimentation modeling using the Water and Tillage/Sediment Delivery Model (WATEM/SEDEM), to evaluate the impact of sediment control structures such as check dams. Research variables include catchment area, population, annual rainfall, average daily evaporation, mainstay surface water availability, land surface erosion rate, sediment volume deposited in the reservoir, effective age of the Batujai Reservoir, and changes in land use in the Dodokan Sub-watershed. The results of this research will provide a better understanding of the main sources of sedimentation in the Batujai Reservoir and the impact of land use changes on the reservoir. It is hoped that the recommendations for sedimentation management strategies resulting from this research will help maintain reservoir storage capacity, which is important for meeting various water needs in the region.